Assessment of Breast Doses in Mammography Screening (Bangladesh Journal of Nuclear Medicine, 2018)
Thermoluminescent dosimeters (TLD-100H) were in use for the assessment of average glandular dose to breast in mammography screening with GE machine, King Abdul Aziz University Hospital for 45 mm breast compressed thickness, 26 kVp, 100 mAs and Mo/Mo target/filter combination. Reader’s calibration factor for the TLDs was generated with the same exposure parameters using RadCal mammo ionization chamber as reference. The calibration factor was reproduced within 3% standard deviation. Several sets of selected TLD-100H placing in different configurations were exposed to X-ray beam under identical exposure condition as it was used for generation of calibration factor. The entrance surface doses were calculated by using the measured net TL-response and the calibration factor. Thereafter, the average glandular doses (AGD) were calculated. The measured average entrance surface dose (AGD) at the reference position (6 cm laterally centered from the chest edge wall) was 7.704 mGy with less than 2% standard deviation. The calculated average glandular dose to the breast at the reference location has been found to be 1.429 ± 0.037 mGy.Bangladesh J. Nuclear Med. 18(2): 161-167, July 2015